Multicentre investigation of carbapenemase-producing Escherichia coli and Klebsiella pneumoniae in German hospitals - Kaase, Martin; Burckhardt, Irene (International journal of medical microbiology, 2016)
Aim of this study was to determine the incidence and molecular epidemiology of carbapenemase-producing Escherichia coli and Klebsiella pneumoniae in Germany. E. coli and K. pneumoniae isolates from clinical samples which were non-susceptible to carbapenems were collected in laboratories serving 20 hospitals throughout Germany from November 2013 to April 2014. The isolates were tested for the presence of carbapenemases by PCR and phenotypic methods and typed by multilocus sequence typing. Risk factors including a previous hospitalization abroad were analysed. Carbapenemases were detected in 24 isolates from 22 patients out of 464,514 admissions. Carbapenemases included OXA‐48 (n=14), KPC‐2 (n=8) and NDM‐1 (n=2). Except for two K. pneumoniae isolates with ST101, all OXA‐48 producing strains belonged to different clones. In contrast, half of KPC‐2 producing K. pneumoniae were of ST258 and both NDM‐1 producing strains were of ST11. Compared to carbapenem-susceptible controls, patients with carbapenemase-producing strains differed by a significantly higher proportion of males, a higher proportion of isolates from wound samples and a more frequent previous stay abroad in univariate analysis. This multicentre study demonstrated an incidence of carbapenemase-producing E. coli and K. pneumoniae from clinical samples in Germany of 0.047 cases per 1000 admissions. OXA‐48 was more frequent than KPC‐2 and NDM‐1 and showed a multiclonal background.